Developing Intercultural Awareness through Representations of Christmas Culture in German Supermarket Advertisements - Wilma Prisca Anavi; Dewi Kartika Ardiyani (Randwick International of Social Science Journal, 2026)
ABSTRACT This study aims to reveal the relevance of German Christmas cultural representations in Christmas-themed supermarket advertisements as intercultural learning materials. Actual materials that reflect the culture in context are needed so that learners can effectively improve their intercultural understanding. Using a descriptive qualitative approach, content analysis was applied to German supermarket advertisements published in 2024 entitled “Magische Weihnachtszeit” (Lidl) and “Feiert Weihnachten, wie ihr wollt” (Edeka). Both advertisements can be viewed on YouTube, which provides easy access to the video advertisements as learning materials. The selection of Christmas-themed advertisements was based on the similarity between annual celebrations in Germany and Indonesia, namely the celebration of Eid al-Fitr. This similarity makes it easier for learners with an Indonesian cultural background to reflect on cultural perspectives, thus enabling more effective intercultural learning. It was found that the Lidl and Edeka advertisements can be used as alternative culture-based learning materials because they contain cultural representations that can train students' understanding of sociopragmatic and sociolinguistic concepts, cultural practices, and cultural features. According to the CEFR, these concepts are key to intercultural understanding. The results show that Lidl and Edeka advertisements can be used as material for intercultural learning. The German Christmas culture represented in Lidl and Edeka advertisements can help learners, especially those at levels A2 to B2, to strengthen their understanding of the language and culture